’Built to Last‘: Paradigm or Panacea? - Morden, Tony (International journal of value-based management, 1997)
This article describes the prescriptive model of the ’visionary company‘proposed by Collins and Porras in their influential 1994 study ’Built toLast‘. The article notes the U.S. bias of this model; and comments on theuniversalistic contention of the authors that ’the basic dynamics of being avisionary company will hold up across cultures and nationalities‘. Thearticle evaluates and qualifies the universalistic propositions of Collinsand Porras, and places the ’Built to Last‘ study in a wider internationaland cross-cultural context.